Fodor's Florence & Tuscany 2024 - Humphreys, Liz; Rucidlo, Patricia; Shemaria, Liz (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2024)
"Now fully redesigned with a new layout and beautiful images, this guide is packed with customizable itineraries with top recommendations, detailed maps of Florence and Tuscany, and exclusive tips fromlocals"--